POTENSI LIMBAH KULIT PISANG KEPOK (Musa paradisiaca) SEBAGAI BAHAN BAKU PEMBUATAN ASAM ASETAT MENGGUNAKAN BERBAGAI MACAM STARTER - Ilham '; Itnawita '; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Kepok banana  (Musa  paradisiaca)  peel  waste contain sugar that can  be  changed  to acetic acid using Effective Microorganism (EM-4), kombucha (KO), cassava yeast (RT) and instant yeast  (RI)  (commercial  starter). The Commercial  starter  contains variety of bacteria and yeasts  with different content of microorganism  that will influence  the amount of ethanol  produced.  The aim of this study  to  determine the  potential of kepok banana peel  waste used as the main material  in synthesis  of acetic acid using commercial  starter.  Based on the  fermentation  results  using  the four starter,  cassava yeast  has  a  good  ability  to  be  fermented.  The acetic acid formation was  obtained  under condition which substrate and starter amount are 80% w/v and 5 grams respectively and fermentation  time  4  day.  Based on these conditions  it was found that the amount of organic acid total  determined  by  titrimetric  method  is  4.712±0.066%  and  acetic  acid formed which was determined by Ion Chromatography method is 0.7507± 0.0538%.